Seismic behavior of interior concretebeam-column joints with non-seismic and limited seismic detailing - Li, Qingyuan. (2009)
Reinforced concrete structures are very common in a region of low to moderate seismicity, and are the predominant structural system in Singapore and Malaysia. Recent post-earthquake investigations indicated that extensive damage occurred as a result of excessive shear deformation and severe strength degradation of the beamcolumn joints in non-seismically detailed frames, thus leading to full collapse of structures. The BS 8110 code used in Singapore and Malaysia does not specify any provisions for seismic design or detailing of reinforced concrete structures. Therefore, it is of great concern that the strength, ductility, and energy dissipation capacity of these structures may not be adequate to sustain earthquake-induced loads in regions of low to moderate seismicity. The need for evaluating and improving detailing of existing structures is obvious.